What makes courier service creative?—From managing logistics to managing knowledge - Yao, Liu; Mohd Shah, Nurul Izzah; Mohamad, Fazeeda; Cheng, Jack Kie; An, Hong Ki; Abdalla, Ahmed N. (MDPI, 2022)
The recent online business blossom has stimulated the soaring demand for logistics service, or rather, courier service, which emerged as a robust momentum of economic growth worldwide. So, to satisfy the fast-changing online businesses, courier services have been urged to be more creative to ensure the desired efficient movement of goods and services along the supply chain, especially in logistics and parcel deliveries. How could the courier service be more creative? What makes courier service creative has not yet been fully explored. Therefore, this study aimed to unveil the antecedents of creativity of courier services from the perspective of managing knowledge which is regarded as the source of wisdom. Taking into consideration the logistical nature of courier service, the proposed framework integrates logistics into knowledge management, and focuses on empirically detecting its relationship with creativity in the context of Malaysia. The results prove that the logistics-related knowledge management (LRKM) affects creativity in a significant and positive manner. However, amongst the four select constructs, only the logistics-related knowledge dissemination (LRKD) followed by the logistics-related knowledge responsiveness (LRKR) are significant operational contributors in the development of creativity in courier services. The logistics-related knowledge generation (LRKG) and logistics-related shared interpretation (LRKS) have not yet appeared significant, which is mainly due to the current insufficient development of the courier service in Malaysia. It indicates that to further enhance creativity, courier service providers should attach importance on managing knowledge of logistics operation, especially in the respects of dissemination and responsiveness, while more efforts shall be exerted to the generation and shared interpretation as both are still having positive potentials towards creativity. This study is amongst the pioneers to cross-extend the theory of logistics management and knowledge management into the courier service industry, and it also expands the application of the theory of creativity into the courier service industry. Future study could further examine the inter-relationships among the detected constructs, the effects of creativity of courier service on the performance of e-business firms, and so on.